Distance Learning: Responsibilities and Challenges Facing Educators in the 21st Century - Hiani, Karim El (Journal of Education and Vocational Research, 2015)
The emergence of distance learning has brought to the fore new responsibilities and challenges that must be taken into consideration by educators especially at the university level (White, 2003; Larreamendy-Joerns & Leinhardt, 2006). Thus, two main questions might need to be risen: what are the new roles of educators with regard to distance learning? Also, what are the challenges that face educators in distance learning? Hence, the present paper goes through the new roles and responsibilities that distance learning educators need to bear in mind to make an outstanding contribution in the learning process. Basically, educators are in dire need of the use of new mediums and skills. Additionally, this paper deals with the main challenges facing educators in the area of distance learning. The emergence of the latter comes not to be free of some constraints including issues related to planning, teaching, and evaluating. Raising an explicit awareness towards these responsibilities and challenges plays a tremendous role in promoting the status of distance learning. This paper provides beneficial implications for educators, curriculum designers, and stakeholders in that it provides a good platform to reconsider serious issues related to distance learning education.